Emergency department attendance by callers to NHS111 who end the call prior to triage: A time-to-event-analysis - Richard Pilbery; Jen Lewis; Rebecca Simpson (PLoS ONE, 2026)
Background The English National Health Service (NHS) 111 telephone service aims to assist members of the public with urgent medical care needs. However, each year nearly 18% of the 20.6 million calls to NHS 111 are abandoned prior to speaking to a health advisor. There are concerns that callers who are not triaged may not appropriately seek the correct level of care for their needs. The aim of this study was to explore the patient journey for callers who contact NHS 111 but end the call prior to speaking to a health advisor. The primary objective was to determine whether ending an NHS 111 call prior to triage impacts the time taken for a patient with urgent healthcare needs to attend an Emergency Department (ED). Methods We obtained routine data pertaining to all NHS 111 calls made by adult patients registered with a General Practitioner (GP) in the Bradford region of Yorkshire, England, between the 1st January 2022 and 30th June 2023. Subsequent healthcare access in the 72 hours following each caller’s first (index) call was identified using the Connected Bradford research database. We conducted a time-to-event analysis comparing the two cohorts: those whose index call was triaged by an NHS 111 health advisor vs. callers who ended the index call prior to triage. The ‘event’ was defined as an ED attendance within 72 hours for a non-avoidable cause. We utilised Kaplan–Meier (KM) curves and conducted log-rank tests to compare the time to first non-avoidable ED attendance between cohorts, and a Cox proportional hazards model adjusted for baseline characteristics. From this, we calculated the adjusted hazard ratio (aHR) of attending an ED with a non-avoidable cause. Results There were 19,056 index non-triaged and 168,609 triaged calls made to NHS 111 by an adult registered with a Bradford GP. A higher proportion of ED attendances in the triaged call cohort were non-avoidable compared with the non-triaged cohort (84.6% compared to 80.0% for triaged calls). In addition, callers in the non-triaged call cohort attended ED later than the triaged call cohort (median 10 vs 8 hours, p < 0.001 by log rank test). The aHR for non-triaged calls vs triaged calls was 0.32 (95%CI 0.30–0.34). Conclusion The time-to-event analysis found that callers to NHS 111 who do not wait to be triaged are slower to attend ED with a non-avoidable cause than those who are triaged, and are more likely to attend ED with an avoidable cause than triaged callers. This suggests that, for patients with a serious health problem that would be considered non-avoidable at ED, triaging by NHS 111 was associated with a reduced time to ED attendance.